The Crown and the Courts: separation of powers in the early jewish imagination - Flatto, David C. (Harvard University Press, 2020)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Introduction: Law and Power in Biblical and Western Jurisprudence -- Part One. Second Temple Literature -- 1. Postbiblical Jurisprudence -- 2. Philo's Jurisprudence -- 3. Qumran Literature on Kingship, Councils, and Law -- 4. Josephus on Kingship, Theocracy, and Law -- Part Two. Rabbinic Literature -- 5. Kingship and Law in Tannaitic Literature -- 6. Juridical Models in Tannaitic Literature -- 7. The Nasi and the Judiciary in Rabbinic Literature -- Part Three. Roots, Theory, Afterlife -- 8. Formative Factors -- 9. Ancient and Modern Jurisprudence -- Conclusion -- Abbreviations -- Notes -- Acknowledgments -- Index of Names and Terms -- Index Locorum.